2014
DOI: 10.3892/br.2014.404
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic knee osteoarthritis following anterior cruciate ligament injury: Potential biochemical mediators of degenerative alteration and specific biochemical markers

Abstract: As a common injury, anterior cruciate ligament (ACL) injury is unable to heal itself naturally, which possibly increases knee instability, accelerates the risk of joint degeneration and leads to knee osteoarthritis (OA) in the ACL-injured knee. Thus, ACL reconstruction using an autograft or allograft tendon is proposed to maintain the biomechanical stability of the knee joint. However, previous studies demonstrate that surgical management of ACL reconstruction failed to abrogate the development of OA completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…While proposed mechanisms include changes in tibiofemoral mechanics, concurrent injuries, or patients' innate risk factors such as BMI and bony morphology 2,8,9 , there is increasing evidence that posttraumatic OA in patients with ACL injury may result from a cascade of biomechanical and biochemical changes following ACL injury 10,11 . In particular, sustained intraarticular inflammation is suggested to activate matrix metalloproteinases (MMPs) that in turn digest collagen and proteoglycan components of the cartilage matrix, culminating in cartilage damage associated with OA 12 . However, to date it is not clear what triggers and maintains this detrimental flare of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…While proposed mechanisms include changes in tibiofemoral mechanics, concurrent injuries, or patients' innate risk factors such as BMI and bony morphology 2,8,9 , there is increasing evidence that posttraumatic OA in patients with ACL injury may result from a cascade of biomechanical and biochemical changes following ACL injury 10,11 . In particular, sustained intraarticular inflammation is suggested to activate matrix metalloproteinases (MMPs) that in turn digest collagen and proteoglycan components of the cartilage matrix, culminating in cartilage damage associated with OA 12 . However, to date it is not clear what triggers and maintains this detrimental flare of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supports an increasing likelihood of cartilage damage with greater time from ACL injury[4, 5] and delayed ACL reconstruction increases the risk of meniscus and cartilage injuries due to persistent instability[6]. However, ACL reconstruction does not prevent the progression of OA[7, 8], suggesting that the increased risk of OA following ACL injury is not due to joint instability alone[9].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models, in which hyaline articular cartilage (HAC) was experimentally impacted [14] or joint instability was experimentally induced [5], showed rapid progression of joint damage, at the level of the cartilage and subchondral bone [2, 68]. Surgical management to achieve stabilization of the knee failed to abrogate the development of post-traumatic osteoarthritis (PTOA) [9, 10], indicating that a biochemical disturbance in the HAC of the affected joint is implicated in the accelerated rate of joint degeneration. Longitudinal studies in human medicine have shown that the initial cartilage damage progresses to an established degenerative joint disease (DJD) in the hip [11] and knee joints [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Resident chondrocytes are activated to produce inflammatory cytokines, such as IL-1ß, IL-6, TNF-α [16]. These cytokines participate to recruitment of inflammatory cells, and activation of intracellular pathways promoting the expression of metalloproteinases [MMPs −1, −3, −9, −10, −13 and aggrecanases (ADAMTs)] activating procollagenase [10, 17] and cathepsin K [18], lastly degrading proteoglycans (PGs) and type II collagen, in the cartilage matrix. Further mechanical stress on the weakened cartilage matrix produces progressive loss of the HAC [13, 19], and the release of extracellular matrix molecules in the synovial fluid (SF).…”
Section: Introductionmentioning
confidence: 99%